Hopping conduction distance of bipolar switching GdOx resistance random access memory thin films devices modified by different constant compliance current. (December 2018) - Chen, Kai-Huang; Cheng, Chien-Min; Li, Cheng-Ying; Huang, Shou-Jen
Abstract: Bipolar switching properties and electrical conduction mechanism of the gadolinium oxide thin film prepared by rf sputtering technology for applications in resistive random access memory devices was investigated in different constant compliance current. The electrical and physical properties of gadolinium oxide thin film were determined by current versus applied voltage ( I-V ) and XPS measurement. To discuss the electrical conduction mechanism for different constant compliance current, the typical electrical switching curves of gadolinium oxide thin films RRAM devices for different temperature was transferred to fitting. Finally, the activation barrier energy, hopping conduction distance and non-volatile characteristics between the electrons transmission switching behavior in initial metallic filament forming path of the gadolinium oxide thin film RRAM devices was described and explained in physical diagram model. Highlights: The I-V curves of gadolinium oxide thin films RRAM devices for 2mA compliance current parameters was exhibited the ohmic conduction, schottky emission conduction, and hopping conduction for low and high applied voltage in curves fitting. The electronic activation energy barrier equation (Ea) and the hopping conduction distance (Δz) for 2mA compliance current were 139 meV and 3.38 ± 0.5 nm, respectively. For 10mA compliance current, the hopping conduction distance (Δz) value was 0.71 ± 0.1 nm. The electronic activation energy barrier equation (Ea) and the hopping conduction distance (Δz) diagram of the RRAM devices were well also assumed and explained.